2019
DOI: 10.29252/ijwph.11.4.233
|View full text |Cite
|
Sign up to set email alerts
|

Explanation of the Managerial Competencies of Healthcare Staff to Discounting the Number of Martyrs and Veterans in the Iran-Iraq War: A Qualitative Study

Abstract: Mortality and injuries among Iranians in Iran-Iraq ... [2] Years of life lost among Iranian people killed in ... [3] Roy's adaptation model-guided education on … [4] Development of adaptation questionnaire using Roy's adaptation ... [5] Effect of Roy's adaptation modelguided education ... [6] Exploring coping strategies of healthcare providers with tension sources ... [7] The evaluation of application of coordination based disaster response ... [8] Nurses' perceptions of care during wartime: a qualitative … [9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Guba and Lincoln's criteria, which included credibility, transferability, dependability, and confirmability, were considered to increase the study's trustworthiness [18,19]. To enhance the credibility, the researchers considered diversity in sampling, established relationships with the participants, used data collection and researcher triangulation, persistent observation, searched for documents and evidence, analyzed negative cases, reflected on the credibility of the researchers (all the researchers were engaged in education or managerial affairs in the study setting during the COVID-19 pandemic).…”
Section: Trustworthinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Guba and Lincoln's criteria, which included credibility, transferability, dependability, and confirmability, were considered to increase the study's trustworthiness [18,19]. To enhance the credibility, the researchers considered diversity in sampling, established relationships with the participants, used data collection and researcher triangulation, persistent observation, searched for documents and evidence, analyzed negative cases, reflected on the credibility of the researchers (all the researchers were engaged in education or managerial affairs in the study setting during the COVID-19 pandemic).…”
Section: Trustworthinessmentioning
confidence: 99%
“…Novel coronavirus (nCoV), is also called coronavirus disease 2019 (COVID- 19). The first reported outbreaks occurred in China in December 2019.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Therefore, it is very important to increase the competence of nurses in providing PFA during a disaster. 26 Competence consists of the dimensions of knowledge, skill, attitude, mission commitment, leadership, management ability self-identity of dual roles (such as obedience, empathy, etc), 27,28 critical thinking, innovation, and personality traits appropriate to the work field. 29 No study was found that investigated the level of competence of nurses in providing PFA.…”
mentioning
confidence: 99%